“Masamper: Seni Vokal Sangihe Talaud sebagai Media Pelestarian Budaya dan Pendukung Pastoral Konseling Kontekstual” - Samuel Wailan Leonard Wanget; Lumenta, Anita; Christian Onsu; Rhea Salsa Natalia Susmantoyo (POIMEN Jurnal Pastoral Konseling, 2024)
Masamper, a distinctive vocal art form endemic to the Sangihe Talaud community of North Sulawesi, holds significant cultural and spiritual value. Rooted in oral tradition and predating Christian influence, Masamper has evolved to incorporate elements of diatonic music introduced by 19th-century Dutch missionaries. This fusion has made it an integral part of local church services. As a cultural expression, Masamper embodies social, aesthetic, and religious values, contributing to community harmony and identity. A pastoral counseling perspective suggests that Masamper can facilitate emotional recovery, introspection, and communal solidarity. This tradition serves as an effective medium for theological exploration, healing, and reconciliation within church settings. By integrating Masamper into congregational life, pastoral care becomes more contextual, relevant, and transformative, enabling communities to both cherish their cultural heritage and address contemporary challenges. Masamper transcends its status as a mere tradition; it is a spiritual expression that fortifies the faith and identity of the community. This qualitative study, employing a literature review approach, delves into the history, function, and role of Masamper within the Sangihe Talaud community. The analysis reveals that Masamper plays a crucial role in preserving local traditions in the face of globalization and serves as a vehicle for conveying moral and theological values. In church services, Masamper functions as a medium of worship and spiritual instruction. Its poetry, imbued with Gospel values, significantly impacts congregational understanding.